Estudio de casos sobre la enseñanza del inglés en la formación de máster en educación ambiental - Montejo Lorenzo, Manuel Narciso; Risco Soria, Roxana (Transformación, 2024)
The article describes a part of the result of a bibliometric study of the total number of theses presented as the graduation exercise by the participants of the third edition of Environmental Education Master Training Program, particular the results connected with role of the English Language in accessing, processing and communicating information. The results are compared to the objectives and contents of the English language syllabus used at the training program. By means of the methodology delivered by the Master Training Program Committee, and the use of bibliometric techniques a quantitative study of the whole population was carried out, later on the same basis a case study was completed involving two graduates of high, medial and low results in English. The authors arrived at conclusions in relation to the effectiveness of the English syllabus and the way graduates make use of English as a research tool.